Strategi Kebijakan: Integrasi Kurikulum Modern di Pesantren sebagai Pilar Transformasi Pendidikan Islam di Era 5.0 - Muh. Yahya (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper outlines that the transformation of Islamic education in the digital era requires Islamic boarding schools (pesantren) to integrate a modern curriculum without sacrificing traditional Islamic values. This study analyzes the policy strategy for integrating a modern curriculum in Islamic boarding schools as a response to the challenge of ensuring the relevance of graduates to the demands of the times. The study methodology uses a qualitative approach with USG (Urgency, Seriousness, Growth) analysis developed to identify problem priorities, root cause analysis using a fishbone diagram, and evaluation of policy alternatives based on William N. Dunn's criteria. Data were obtained through a study of educational policy documentation, institutional performance reports, and a review of academic literature. The analysis shows that the main problem lies in the absence of operational regulations that guide the integration of a modern curriculum in the Islamic boarding school education system. The study recommends the Minister of Religious Affairs Regulation on the Integration of a Modern Curriculum in Islamic Boarding Schools as the most strategic policy instrument to bridge tradition and modernity in Islamic education towards Indonesia Emas 2045.